2020
DOI: 10.1109/tns.2020.3027243
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Equivalence of Terrestrial Radiation Tolerance Experiments

Abstract: High energy (>40 MeV) protons are commonly used to characterize space electronics' radiation tolerance against damage caused by energy transfer to the nuclei and electrons of semiconductor materials while in orbit. While practically useful, these experiments are unrepresentative in terms of particle type and energy spectra, which results in disproportionate amounts of displacement damage and total ionizing dose. We compare these damages to those realized by bulk semiconductors used in optoelectronics in common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Ideally to assess fitness for operation in space, one would induce damage with the same particle distribution (type and energy) as the component would be subject to in the particular earth orbit anticipated. Typically, high-energy (>50 MeV) protons are used, although we have previously shown that lower energy protons provide a more representative ratio of nuclear to electronic energy deposition to that incurred by the total radiation environment in orbit [20]. This being the case, the particles used here while certainly not the same as those seen in orbit, do not do a worse job at approximating the damage done in orbit than do typical radiation tolerance characterizations.…”
Section: A Rutherford Backscatter Channelingmentioning
confidence: 97%
“…Ideally to assess fitness for operation in space, one would induce damage with the same particle distribution (type and energy) as the component would be subject to in the particular earth orbit anticipated. Typically, high-energy (>50 MeV) protons are used, although we have previously shown that lower energy protons provide a more representative ratio of nuclear to electronic energy deposition to that incurred by the total radiation environment in orbit [20]. This being the case, the particles used here while certainly not the same as those seen in orbit, do not do a worse job at approximating the damage done in orbit than do typical radiation tolerance characterizations.…”
Section: A Rutherford Backscatter Channelingmentioning
confidence: 97%
“…There is also a need to revise some of the existing radiation test methods. [86][87][88][89] For heavy ion testing, one standard for the circuitry is MIL-STD-750 TM1080. This method provides a framework for standardized testing of heavy ion irradiation of power MOSFETs to establish SEB and SEGR.…”
Section: Radiation Test Standardsmentioning
confidence: 99%
“…In the space radiative environment, there are many high energy particles (especially protons) which induce the major problem for the use of electronic components embedded in space systems [10]. The reason determining *Corresponding author at: clara.bataillon@ies.univ-montp2.fr the radiation tolerance of an electronic device remains under investigation [11].…”
Section: Introductionmentioning
confidence: 99%